The experimental analysis applied to an evacuated tube solar collector equipped with solar parabolic trough and carbon filter for purification of water - et. al., Sharayu D. Wasu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Carbon filters are vital at eliminating elements such as chlorine, radon, benzene, solvent, compounds, volatile organic chemicals, pesticides, herbicides, lots of man-made chemicals and a particle are contact with tap water and removes the bad tastes and odor of the water. Initially by carbon filter water is purified then passed to evacuated vacuum tubes for further purification. A solar thermal collector is parabolic trough with a polished mirror-like finish metal straight in one dimension and curved as a parabola in the other two dimensions. The energy of sunlight reflects and focused along the focal line on vacuum tube